Note sulla nozione di “dialettica” in Lenin - Giangrande, Matteo (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2018)
In Lenin’s works, Dialectics means a) scientific method and b) historical process. Diverging from the metaphysical method and from the reactionary doctrinarianism of non-dialectical Socialists, Marxist materialist Dialectics is a critical and historical-concrete analysis of the living contradictions animating conflicts between social classes: an omnilateral reason, opposed to the eclectic unilaterality of formal logic. Dialectics as Marxist theory of knowledge identifies the causes of historical process in the conflicting unity of elements contradicting each others. Social evolution is not a gradual transformation from simple to complex: quite the contrary, the historical development of social life is dialectic, because it is driven by objective contradictions between classes, revolutionary leaps, and laws conditioning the individual way of being. Keywords: Dialectic, scientific method, historical process, living contradiction, omnilateral reasoning.